Jewish women in comics : bodies and borders - Bauer, Heike; Greenbaum, Andrea; Lightman, Sarah 1975- (Syracuse University Press, 2023)
"In this groundbreaking collection of essays, interviews, and artwork, contributors draw upon a rich treasure trove of Jewish women's comics to explore the representation of Jewish women's bodies and bodily experience in pictorial narratives. Spanning national, cultural, and artistic borders, the essays shine a light on the significant contributions of Jewish women to comics"--